A rare complication of Yellow Phosphorous poisoning. (April 2022) - Kumar, Aswin; Gangadharan, Harikrishnan; Manju, Remya; Prakash, Akhil; Arasan, Saravana S; Kumar, Satish
Yellow phosphorous is one of the most common toxins reported to cause fulminant hepatic failure. Yellow phosphorous is a component of rodenticides and fireworks, and is freely available over the counter. The mortality rate as high as 27% from fulminant hepatic failure has been reported following ingestion of yellow phosphorous. 1 Multisystem toxicity affecting gastrointestinal, cardiac, renal and central nervous systems occurs. 2 There is a paucity of literature on its haematological toxicity. In this case report, we highlight the clinically significant myelosuppression observed in a patient resulting from yellow phosphorous; a small literature review has also been done on this rare complication.